Urgensi Pembentukan Karakter Religius Peserta Didik melalui Pembelajaran Al-Qurân Hadits di Madrasah Ibtidaiyah - Fauziah, Irma (Sekolah Tinggi Ilmu Tarbiyah Ibnu Sina Malang, 2023)
This research is motivated by the fact that the decadence of the religious character of today's children does not reflect the nation's successors who are good and have good character. The purpose of this research is to describe the urgency of learning Al-Quran Hadith in forming religious character, methods of forming character as well as supporting and inhibiting factors in learning Quran Hadith at Madrasah Ibtidaiyah level. The method used in this research is the library research method. The data were obtained from books and scientific articles from the internet that were relevant to the research discussion. The data search method uses the Publish or Perish application to access data collections and sources of information from journals from the Crossref and Google Scholar databases by inputting the keywords